2018
DOI: 10.1016/j.lungcan.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Malignant cells from pleural fluids in malignant mesothelioma patients reveal novel mutations

Abstract: Short term cultures of tumour cells from MM pleural effusions offer an accessible alternative to surgical tumour biopsies in the study of MM genomics and reveal novel mutations of interest. Pleural effusion tumour cells provide an opportunity for the monitoring of tumour dynamics, treatment response and the clonal evolution of MM tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…11 What is surprising in our results is the absence of the TRAF7 and CDC42 alterations reported by Yu et al 7 and Stevers et al 11 in WDPM and by the same group in adenomatoid tumors 31 . Alterations in TRAF7 has also been reported in malignant mesotheliomas 4,20,32…”
Section: Discussionmentioning
confidence: 83%
“…11 What is surprising in our results is the absence of the TRAF7 and CDC42 alterations reported by Yu et al 7 and Stevers et al 11 in WDPM and by the same group in adenomatoid tumors 31 . Alterations in TRAF7 has also been reported in malignant mesotheliomas 4,20,32…”
Section: Discussionmentioning
confidence: 83%
“…Comprehensive patient demographics have been detailed previously. 18 Somatic mutation burden was not associated with a survival benefit. 18 Predicted neoantigens identified in all patient samples…”
Section: Patient Characteristicsmentioning
confidence: 87%
“…Over 90% of MM patients develop pleural effusion during the course of their disease, which can be a rich source of cells shed from the primary tumor 17 and we have previously shown that the tumor cells found in the malignant pleural effusions of MM patients carry many of the hallmark mutations found in solid MM tumors, as well as a wealth of novel individual mutations. 18 In our murine MM model, we have previously demonstrated a strong spontaneous endogenous CD8+ T cell response to a predicted MM tumor neoantigen. 19 A recent sequencing study of 98 primary human MM tumor samples found that 59% of all identified somatic mutations resulted in predicted MHC class I-binding neoantigens.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations